The Optimal Capacitors Allocation and Sizing in Radial Distribution System for Power Losses Reduces - Astrid, Erita; Solihin, Muhammad Dani; Siregar, Rosma; Waluyo, Bakti Dwi (Jurnal Teknik Elektro Indonesia, 2023)
The use of capacitors in electrical systems is widely known for their function to improve power factor and voltage profile while minimizing power losses. It results from the reactive power correction provided by capacitors within the system. It is believed that proper placement and size of capacitors can enhance the electricity quality in power systems. Therefore, numerous methods have been developed regarding the allocation and sizing of capacitors. In this research, a meta-heuristic method, Particle Swarm Optimization (PSO) is applied to find the optimal allocation and sizing of capacitors in order to reduce losses. The method has also been improved by modifying the value of inertia weight to optimize the algorithm's performance in finding the solution. The method is tested on an IEEE 34 bus radial distribution system to observe its performance and effectiveness in identifying the solution. The power loss in the distribution system plays the most important role in the economic operation of the power system. It will be used as a fitness function for each particle in the algorithm. The obtained test results include the size of the capacitor and the optimal placement of the capacitor installation.